Graduate mobility: Where do dentistry graduates choose to practise?. (9th July 2019) - Veerasamy, Arthi; Loch, Carolina; Adam, Lee; Brunton, Paul Anthony
Abstract: Background and objective: The international higher education market has grown and developed rapidly. International students generate attractive income for host universities, and gaining an international education benefits students in an increasingly globalised world. However, there is little research regarding where international students intend to work and settle beyond graduation. This study investigated where dentistry students intended to practise after graduation, and whether international students who graduated between 2001 and 2016 are currently practising in their host country (New Zealand) or have migrated overseas. Methods: A cross‐sectional survey was used to investigate current students' intended destination of practice after graduation. Additionally, names of international graduates since 2001 were matched against the 2017 register of practitioners to determine if they were currently registered to practise in their host country. A frequency and bivariate analysis was conducted. Results: Almost 64% of current international students indicated their intention to stay in their host country after graduation. However, only 22% of graduates since 2001 were currently practising in New Zealand. The number of international graduates who registered to practise in New Zealand increased between 2001 and 2016. Conclusion: Less than one‐quarter of international graduates were currently practising in their host country; however, longitudinal data showed that this is an increasing trend. These findings can be used to inform how we might prepare current and future graduates for both local and globalised labour markets.